SOCS3 Suppression Promoted the Recruitment of CD11b+Gr-1−F4/80−MHCII− Early-Stage Myeloid-Derived Suppressor Cells and Accelerated Interleukin-6-Related Tumor Invasion via Affecting Myeloid Differentiation in Breast Cancer - Zhang, Wenwen; Jiang, Mengmeng; Chen, Jieying; Zhang, Rui; Ye, Yingnan; Liu, Pengpeng; Yu, Wenwen; Yu, Jinpu (Frontiers in Immunology, 2018)
IL-6 is an important trigger for the expansion and recruitment of myeloid-derived suppressor cells (MDSCs), which are regarded to be major coordinators of the immunosuppressive tumor microenvironment. In this study, we constructed IL-6-knockdown breast cancer mice models to explore the molecular events involved in the IL-6-mediated effect on MDSC development. We defined a subset of early-stage MDSCs (e-MDSCs) in breast cancer tissues containing the CD11b+Gr-1-F4/80-MHCII- immature phenotype that skewed to acquire a monocytic phenotype upon GM-CSF stimulation in vitro. Tumor-derived IL-6 impaired the differentiation of myeloid progenitors, promoted the accumulation of e-MDSCs locally, and induced more potent T cell suppressive capacity than conventional CD11b+Gr-1+ MDSCs in vitro and in vivo. Tumor-derived, IL-6-inducing SOCS3 suppression and aberrant hyperactivation of the JAK/STAT signaling pathway played vital roles in the development of e-MDSCs. After blocking the IL-6/STAT3 signaling pathway with the IL-6R antibody and STAT3 antagonist JSI-124 in tumor-bearing mice, significant shrinkage of primary mammary tumors and decrease in lung metastatic nodules were observed in vivo, accompanied by the dramatic inhibition of e-MDSC recruitment in situ and recovery of anti-tumor T cell immunity. Thus, we concluded that IL-6-induced SOCS3 suppression promoted the accumulation of CD11b+Gr-1-F4/80-MHCII- e-MDSCs by affecting the differentiation of myeloid progenitors and accelerated the growth and metastasis of mammary carcinoma by attenuating T cell-based immune surveillance. Moreover, the IL-6/STAT3 signaling pathway may be a promising candidate target in developing novel therapeutic strategies to eliminate e-MDSCs and improve breast cancer prognosis.